Effect of enzalutamide on health-related quality of life, pain, and skeletal-related events in asymptomatic and minimally symptomatic, chemotherapy-naive patients with metastatic castration-resistant prostate cancer (PREVAIL): results from a randomised, phase 3 trial. Issue 5 (May 2015) - Loriot, Yohann; Miller, Kurt; Sternberg, Cora N; Fizazi, Karim; De Bono, Johann S; Chowdhury, Simon; Higano, Celestia S; Noonberg, Sarah; Holmstrom, Stefan; Mansbach, Harry; Perabo, Frank G; Phung, De; et al.
Summary: Background: Enzalutamide significantly increased overall survival and radiographic progression-free survival compared with placebo in the PREVAIL trial of asymptomatic and minimally symptomatic, chemotherapy-naive patients with metastatic castration-resistant prostate cancer. We report the effect of enzalutamide on health-related quality of life (HRQoL), pain, and skeletal-related events observed during this trial. Methods: In this phase 3, double-blind trial, patients were randomly assigned (1:1) to receive enzalutamide 160 mg/day (n=872) or placebo (n=845) orally. HRQoL was assessed at baseline and during treatment using the Functional Assessment of Cancer Therapy–Prostate (FACT-P) and EQ-5D questionnaires. Pain status was assessed at screening, baseline, week 13, and week 25 with the Brief Pain Inventory Short Form (BPI-SF). The primary analysis of HRQoL data used a mixed-effects model to test the difference between least square means change from baseline at week 61. We assessed change from baseline, percentage improvement, and time to deterioration in HRQoL and pain, the proportion of patients with a skeletal-related event, and time to first skeletal-related event. Analysis was done on the intention-to-treat population. This study is registered withClinicalTrials.gov, numberNCT01212991 . Findings: Median treatment duration was 16·6 months (IQR 10·1–21·1) in the enzalutamide group and 4·6 months (2·8–9·7) in the placebo group. The mixed-effects model analyses showed significant treatment differences in change from baseline to week 61 with enzalutamide compared with placebo for most FACT-P endpoints and EQ-5D visual analogue scale. Median time to deterioration in FACT-P total score was 11·3 months (95% CI 11·1–13·9) in the enzalutamide group and 5·6 months (5·5–5·6) in the placebo groups (hazard ratio [HR] 0·62 [95% CI 0·54–0·72]; p<0·0001). A significantly greater proportion of patients in the enzalutamide group than in the placebo group reported clinically meaningful improvements in FACT-P total score (327 [40%] of 826 vs 181 [23%] of 790), in EQ-5D utility index (224 [28%] of 812 vs 99 [16%] of 623), and visual analogue scale (218 [27%] of 803 vs 106 of [18%] 603; all p<0·0001). Median time to progression in BPI-SF pain at its worst was 5·7 months (95% CI 5·6–5·7) in the enzalutamide group and 5·6 months (5·4–5·6) in the placebo group (HR 0·62 [95% CI 0·53–0·74]; p<0·0001). Progression of pain at its worst was less common in the enzalutamide group than in the placebo group at week 13 (220 [29%] of 769 vs 257 [42%] of 610; p<0·0001), but not at week 25 (225 [32%] of 705 vs 135 [38%] of 360; p=0·068). 278 (32%) of 872 patients in the enzalutamide group and 309 (37%) of 845 patients in the placebo group had experienced a skeletal-related event by data cutoff. Median time to first skeletal-related events in the enzalutamide group was 31·1 months (95% CI 29·5–not reached) and 31·3 months (95% CI 23·9–not reached) in the placebo group (HR 0·72 [95% CI 0·61–0·84]; p<0·0001). Interpretation: In addition to improving overall survival relative to placebo, enzalutamide significantly improves patient-related outcomes and delays occurrence of first skeletal-related event in chemotherapy-naive men with metastatic castration-resistant prostate cancer. Funding: Astellas Pharma and Medivation.